Age of the Purported Zhanjin Formation in Gêrzê County, Tibet： A New Understanding and Its Significance - Shenglong, LUO; Genhou, WANG; Jinhan, GAO; Xunlian, WANG; Hongji, XIAO (Acta geologica Sinica (Beijing), 2015)
The Upper Carboniferous Zhanjin Formation has attracted much attention from geoscientists for containing glacial–marine diamictite and cold-water fauna typified by the bivalve Eurydesma.The presence of this Formation has provided important evidence for determining the northern border of Gondwana.Previous researchers have classified those strata north of Niangrong Co in the Gêrzê region as part of the Zhanjin Formation based on the presence of glacial–marine diamictite, although the absence of biological fossil evidence has defied clear age determination.Our field investigations first discovered large quantities of corals, sponges and bryozoans.All coral fossils were identified as belonging to the Hexacorallia subclass including 13 genera and 25 species, primarily including Conophyllia guiyangensis Deng et Kong, Coryphyllia regularis Cuif, Cuifia columnaris Roniewicz, Distichophyllia norica Frech, Distichophyllia gigas Vinassa de Regny, Pamiroseris rectilamellosa Winkler, Retiophyllia clathrata Emmrich, and Retiophyllia paraclathrata Roniewicz.Extensive biostratigraphic correlations show that the hexacorallia should belong to the Late Triassic, thereby negating the presence of the Zhanjin Formation in the study area.Based on analyses of sedimentary facies and detailed study of the glacial–marine diamictite as supposed by earlier researchers, the limestone blocks and gravels within the facies are slope facies olistostromes and waterway sediments from lime slurry debris flows in the submarine fan rather than primary sedimentary products.Among them, lenticular sandstone should be sequentially distributed waterway sand bodies, indicating that the strata have no glacial–marine diamictite.In addition, the rocks containing the mentioned fossils are just limestone blocks from olistostromes, and limestone gravels from waterways of submarine fans.Such a result further negates the presence of the Zhanjin Formation in the study area, and indicates that the age of the studied strata should be youner than the Late Triassic.Through regional stratigraphic comparisons and the study of tectonic settings of the strata, the sedimentary characteristics of the subject strata, including lithology, lithofacies and fossils, are confirmed to be similar to the widely distributed Sêwa Formation in this region.We thus infer that the strata belong to the Middle–Lower Jurassic Sêwa Formation.This finding is important for both studying paleogeography of Tibet and determining the northern boundary of Gondwana.